Ceftriaxone-induced cholestatic hepatitis in a child: A case report and a review of the literature - Massimo Luca Castellazzi; Carlo Virginio Agostoni; Carlo Virginio Agostoni; Jessica Palella; Daniela Civeriati; Paola Marchisio; Paola Marchisio; Gabriella Nebbia (Frontiers Media S.A., 2022)
Ceftriaxone, a third-generation cephalosporin, is commonly used in pediatric patients and is generally well tolerated. Its more frequent adverse effects are biliary pseudolithiasis, urolithiasis, and hemolytic anemia. On the other hand, ceftriaxone-induced acute cholestatic hepatitis is a very rare condition, especially in children. Here, we describe a case of this condition in a young male child to highlight the importance of suspecting this drug-induced liver injury to achieve a prompt diagnosis.